The globular cluster system of the low-luminosity elliptical galaxy NGC 1427 - Forte, Juan Carlos (2001)
Washington photometry is presented for a large number of globular cluster candidates associated with the low-luminosity elliptical galaxy NGC 1427 in the Fornax cluster. The survey is mostly complete to T1 = 23.5 (V ≈ 24.0) and includes an areal coverage of about 216 arcmin2, centered near the galaxy. Most previous studies have failed to detect any evidence of multiple globular cluster populations in this low-luminosity elliptical, in sharp contrast to the bimodal globular cluster systems commonly found in giant ellipticals. The lack of multimodal cluster populations has been used as the basis for suggesting that the formation mechanisms for low-luminosity and giant ellipticals are significantly different. Our metallicity-sensitive C-T1 photometry (the first such study of a low-luminosity elliptical) reveals a definite bimodal cluster population. The red globular cluster population appears strongly centrally concentrated and practically disappears beyond a galactocentric radius of 120″. The mean color of these clusters is similar to that of the inner galaxy halo. Blue globulars, on the other hand, exhibit a shallower spatial distribution. These clusters share a small negative C-T1 color gradient with the galaxy halo, although they are, on average, some 0.3 mag bluer at all galactocentric radii. The overall mean cluster system metallicity is -0.9 ± 0.2. The specific globular cluster frequency SN is 4.5 ± 0.8, if a distance modulus (V0 - Mv) = 31.0 is adopted. Our results demonstrate that nonunimodal globular cluster populations exist in low-luminosity ellipticals, as well as in giant ellipticals, and thus that the formation mechanisms for these galaxies may share some similarities.